Self-rating capacity building in female volleyball players - Shumova, N. S.; Babieva, N. S.; Baykovskiy, Y. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze benefits of the proposed self-rating capacity building model designed to include the following three stages: preparatory stage; motivations and priorities setting stage; and the self-rating capacity building and progress testing stage. Sampled for the study were the 15-16 year-old Class I women volleyball players. Progress of the sample was tested by the Dembo-Rubinstein Test adapted by A.M. Prikhozhan; and analyzed using 6 tables to rate the following three key techniques: overhead pass/ set; underarm pass/ receive; and attack/ spike; with the sample progress data processed using the standard mathematical statistics toolkit. The progress self-rating capacity building model with its set of objective progress self-rating criteria was found beneficial as verified by the sample progress in the sport mastery and personality growth components even when the outside progress ratings were not fair/ accurate enough.